Achievement Emotions and Peer Acceptance Get Together in Game Design at School - Brondino, Margherita; Dodero, Gabriella; Gennari, Rosella; Melonio, Alessandra; Raccanello, Daniela; Torello, Santina (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2014)
This paper presents a game design experience in primary schools, with children creating game design ideas and prototypes. Children were organized in cooperative groups. Game design tasks were organized following gamification principles, with ad-hoc gamified material. Cooperative learning and gamification served to elicit emotions and social inclusion. This paper measures them as follows. It operationalizes social inclusion with peer acceptance in three different social contexts, measured before and after the game design activity. It tracks achievement emotions experienced during game design at school. Then the paper examines the relationships between achievement emotions and peer acceptance. In this manner, it tackles an open problem in the literature concerning the links between emotions and social well-being in a game design experience. Path analyses indicate that, respectively for received choices and mutual friendships, positive emotions played a significant role in improving children’s social relations, and negative emotions were associated with a significant deterioration of social relations, but only for the extra-school leisure context. The paper concludes assessing the study limits and results in relation to game design with and for children.